Computerized attention measure: a web-based open-source test battery to evaluate students’ attention - Pinelli, Mathieu; Palluel, Estelle; Dessus, Philippe; Joet, Gwenaelle; Eichenlaub, Jean-Baptiste; Brugniaux, Julien V.; Portrat, Sophie (Frontiers in Education, 2025)
Measuring attention at school is essential given the relationship between attention, learning and school achievement. In this paper, we present a new battery called Computerized Attention Measure (CAM), which includes 8 web-based tasks we developed to measure several dimensions of attention that are crucial for school. Two studies were conducted to test the psychometric qualities of the CAM battery in preteens during school time. In the first study, we examined completion rate, reliability, validity, and overall behavioral performance in a sample of 646 preteens. A second study involving 202 preteens was conducted to replicate the main findings of study 1 and to test the psychometric qualities of a new task assessing divided attention. These evaluations of the CAM battery showed variability in completion, but the two studies yielded comparable and overall satisfactory psychometric properties, as indicated by behavioral performance and internal consistency. Validity was supported by inter-task correlations, supporting its applicability in school settings. Future work will need to be cautious in completion during group sessions to reduce loss of data and to evaluate the stability of results over time with test–retest reliability. Despite some limitations, the CAM battery appears to meet several important criteria for evaluating preteens’ attentional performance in a school setting.